A 21-year analysis of the publication patterns and level of scientific evidence in three major oral and maxillofacial surgery journals. Issue 6 (June 2021) - Beteramia, D.; Sklavos, A.; Saha, A.; Hyam, D.
Abstract: High-quality research in surgical sciences is constrained by a number of barriers including funding, blinding, adjusting for surgical experience, and inability to recruit sufficient numbers. As a result, surgeons have been reported to accept lower levels of scientific evidence to validate procedures. Our study analysed the quantity and quality of publications in three journals in Oral and Maxillofacial Surgery over a 21-year period. A retrospective analysis of all issues published between 1998 and 2018 in the International Journal of Oral and Maxillofacial Surgery, the British Journal of Oral and Maxillofacial Surgery and the Journal of Oral and Maxillofacial Surgery was conducted. A total of 14, 324 articles were analysed and grouped according to their National Health and Medical Research Council of evidence. The analysis revealed that there has been a promising increase in both the quantity and quality of publications with statistically significant increases in each of the variables analysed. We found a statistically significant increase in the number of articles published in the most recent decade compared with the previous decade across the three journals. The level of evidence also increased during the study period, with greater numbers of level I and II studies being published in more recent years. These findings were found to be statistically significant ( P ˂ 0.001).